Patient Preference and Mobile Application Use in Hemophilia A: A Cross-Sectional Survey from Eastern Europe - Laszlo Nemes; Helga Hartmann; Hrvojka Kostelac; Tina Roblek (Journal of Patient Experience)
Hemophilia A, a bleeding disorder caused by a deficiency of clotting factor VIII (FVIII), is commonly treated with FVIII prophylaxis. Mobile applications help personalize prophylactic regimens by creating individual pharmacokinetic (PK) profiles. This study evaluated how patients with hemophilia A use mobile applications for PK-guided prophylaxis and explored preferences and patterns of usage across different age groups. Between May and September 2022, patients from Bulgaria, Czechia, Hungary, Lithuania, and Romania participated in a cross-sectional survey. The survey collected information on demographics, documentation preferences (mobile applications or paper diaries), usage patterns, and user satisfaction. Of 84 participants, 40.5% used either a mobile application or paper diary exclusively. Czechia had the highest application usage (94.1%), followed by Romania (50.0%). While 84.2% of the application users were satisfied, many suggested improvements including better medication tracking and smartwatch compatibility. No correlation was found between age and documentation type or application preference. Mobile applications were perceived useful, but physician engagement was higher with paper diaries. These findings suggest potential to enhance mobile applications for better patient–physician interaction and user experience.